1995
DOI: 10.1002/eji.1830250838
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin‐6 receptor strongly increases the production of acute‐phase protein by hepatoma cells but exerts minimal changes on human primary hepatocytes

Abstract: Interleukin-6 (IL-6) interacts with a system of receptors, which include a 80-kDa IL-6-binding subunit (IL-6R) and a transducing element (gp130). The soluble form of IL-6R (sIL-6R) can bind its ligand and induce cellular responses by association with gp130, thus acting as an IL-6 agonist. We and others have previously shown that the responsiveness to IL-6 is different in hepatoma and human primary hepatocytes. We therefore compared the effects of sIL-6R on the two types of cells, and on the B9 hybridoma, anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Human primary hepatocytes were isolated from surgical liver biopsies as previously described (20,21). In brief, liver explants were taken from three patients undergoing partial hepatectomy: two patients for benign tumor, and one patient for local metastasis of colon adenocarcinoma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human primary hepatocytes were isolated from surgical liver biopsies as previously described (20,21). In brief, liver explants were taken from three patients undergoing partial hepatectomy: two patients for benign tumor, and one patient for local metastasis of colon adenocarcinoma.…”
Section: Methodsmentioning
confidence: 99%
“…The sIL-1Ra cDNA was excised from the RSET5a expression plasmid as an Xbal and BamHI fragment, and was cloned in pGEM-7 (Promega Corp., Madison, WI) to generate pRAX/B.GEM. The generation of the GAPDH probe was described previously (21). These plasmids were linearized and transcribed with T3 or SP6 RNA polymerase (Promega) to synthesize the 32 P-labeled riboprobes complementary to GAPDH and IL-1Ra mRNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Primary hepatocytes were isolated as described previously [9,10]. Briefly, liver explants were taken from patients undergoing partial hepatectomy.…”
Section: Human Hepatocyte Primary Culturesmentioning
confidence: 99%
“…Both LIF and IL-11 share numerous biological effects with IL-6 on different tissues [6][7][8], including stimulation of APP synthesis by hepatoma cells [4,5]. However, results obtained with tumour cells can be difficult to interpret, since they are not always reproducible with human primary hepatocytes [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There is also a soluble IL-6R (sIL-6R), which is proteolytically cleaved from the membrane-bound IL-6R. It has been shown that the biological activity of IL-6 results from the direct association of either the sIL-6R/IL-6 complex or the IL-6R/IL-6 complex with the membrane-associated protein, gp130, which transduces the IL-6 signal (Mackiewicz et al 1992, Gabay et al 1995. Furthermore, it has been reported that sIL-6R triggers osteoclast formation by IL-6, indicating that the amount of sIL-6R may modulate the IL-6 effect (Tamura et al 1993).…”
Section: Introductionmentioning
confidence: 99%